Hydrogen storage in graphitic nanofibres - McCaldin, Simon Roger (2007)
There is huge need to develop an alternative to hydrocarbons fuel, which does not produce CO2 or contribute to global warming - 'the hydrogen economy' is such an alternative, however the storage of hydrogen is the key technical barrier that must be overcome. The potential of graphitic nanofibres (GNFs) to be used as materials to allow the solid-state storage of hydrogen has thus been investigated. This has been conducted with a view to further developing the understanding of the mechanism(s) of hydrogen storage in GNFs and modifying the material structure to maximise the amount of hydrogen that can be reversibly stored in the material.